CORAK FEMINISME POST-MODERNIS DALAM PENAFSIRAN FAQIHUDDIN ABDUL KODIR - Lukman Hakim (UIN Sunan Kalijaga Yogyakarta, 2020)
The debate about the interpretation of the Qur'an which is considered gender biased, continues to develop with diverse arguments. Women are considered as the aggrieved party in this negotiation. Women are considered as the second sex (second sex) and become subordinate men. As a result, women are the object of oppression for men. In the context of this debate, Faqihuddin Abdul Kodir came with a new argument in approaching religious texts that were considered gender biased. He introduced the method of qira> ’ah mubadalah to create a balanced relationship between men and women. Therefore, this study would like to explain the products produced by Faqihuddin with this method and find the patterns of feminist thought in several developing feminist theories. To achieve this goal, this study uses the structural exegesis method as an analysis tool to find the influence of interpretation of the text with the interpreter's experience in the context that surrounds it. The method used by Faqihuddin to release women from the shackles of men with the muba method is by placing women in the position of men in verse narration, so that there is a reciprocal relationship. From the form of interpretation conducted by Faqihuddin, this study found that the reconstruction of the meaning that was carried out was basically driven by an effort to release the order of symbols in the text which was understood only in its literal form. This reflects the way that is usually done by post-modern feminists who mock each term that indicates the subordination of women to men.